2023
DOI: 10.1002/phar.2794
|View full text |Cite
|
Sign up to set email alerts
|

Management of noncytotoxic extravasation injuries: A focused update on medications, treatment strategies, and peripheral administration of vasopressors and hypertonic saline

Abstract: Extravasation is the leakage of intravenous solutions into surrounding tissues, which can be influenced by drug properties, infusion techniques, and patient-related risk factors. Although peripheral administration of vesicants may increase the risk of extravasation injuries, the time and resources required for central venous catheter placement may delay administration of time-sensitive therapies. Recent literature gathered from the growing use of peripheral vasopressors and hypertonic sodium suggests low risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 106 publications
(347 reference statements)
0
5
0
Order By: Relevance
“… Patient safety considerations of CVC placement in neonates must consider the proximal port distance relative to the vessel entry point for reliable intraluminal durability. Neonatal loose soft tissue and edema during extended CVC use along with patient positioning changes could cause extravascular extrusion of the CVC proximal port. CVC monitoring should include insertion site inspection, blood aspiration from all ports when possible, infusion line pressure monitoring, and obtaining anticipated clinical response from the infusion. Infusions should be immediately discontinued when extravasation is suspected followed by immediate investigation and activation of mitigation measures to minimize patient morbidity 4 …”
Section: Discussionmentioning
confidence: 99%
“… Patient safety considerations of CVC placement in neonates must consider the proximal port distance relative to the vessel entry point for reliable intraluminal durability. Neonatal loose soft tissue and edema during extended CVC use along with patient positioning changes could cause extravascular extrusion of the CVC proximal port. CVC monitoring should include insertion site inspection, blood aspiration from all ports when possible, infusion line pressure monitoring, and obtaining anticipated clinical response from the infusion. Infusions should be immediately discontinued when extravasation is suspected followed by immediate investigation and activation of mitigation measures to minimize patient morbidity 4 …”
Section: Discussionmentioning
confidence: 99%
“…● a specific anatomical location or pattern of injury; examples include damage due to extravasation of a drug at an intravenous administration site7 and ulceration due to topical aspirin8; this is analogous to witnessing the culprit committing the crime;…”
Section: Between-the-eyes Reactionsmentioning
confidence: 99%
“…Mannitol is frequently administered for neurosurgical ICU patients. In our institution, we use 15% mannitol with an osmolarity of 823 mOsm/L (Baxter, Deerfield, IL, USA), which is lower than the 20% (1369 mOsm/L) osmolarity of definite irritants in a recent study 25) . Administration of hypertonic saline through a CVC is also preferred 10) .…”
Section: Special Consideration Of IV Infusates For Neurosurgical Icu ...mentioning
confidence: 99%
“…Administration of hypertonic saline through a CVC is also preferred 10) . However, access may be limited in urgent situations for IICP control 25) . Recent studies have shown an acceptable safety profile for peripherally administered hypertonic saline even with bolus injection 26,27) .…”
Section: Special Consideration Of IV Infusates For Neurosurgical Icu ...mentioning
confidence: 99%
See 1 more Smart Citation